Parametric investigation of the phase characteristics of a beta-type free piston Stirling engine based on a thermodynamic-dynamic coupled model. (15th March 2021) - Chen, Pengfan; Yang, Peng; Liu, Liu; Liu, Yingwen
Abstract: In this study, to reveal the phase characteristics of a beta-type free piston Stirling engine (β-FPSE), a thermodynamic-dynamic coupled model is proposed and verified experimentally. With the phasor notation method, the influences of the heating temperature, cooling temperature, spring stiffness and damping coefficients on the phases of displacer and power piston, and the output performance are investigated. The results indicate that the phase angles of the displacer and power piston increase with the heating temperature, and decrease with the cooling temperature. In the variation of power piston phase with its spring stiffness, a point of temperature independence (PTI) is identified. In the variation in the power piston phase with the displacer damping coefficient, a point of damping balance (PDB) is identified. A hysteresis of the PDB will occur if the heating temperature increases. In addition, the output power and power angle are obtained at the same damping coefficient of the displacer, which is equal to the displacer damping coefficient at the PDB if the spring stiffness ratio is less than 3.31. Moreover, based on the PV diagrams of different spring stiffness and damping coefficients, the compression ratio and pressure ratio for the optimum output power and efficiency are determined, respectively. Highlights: A PTI is identified in the variation of power piston's phase with k p . A PDB is identified in the variation of power piston's phase angle with d d . A hysteresis of PDB will occur if the heating temperature increases. The d d of PDB and the minimum are equal when k p / k d is less than 3.31.